PEMBERDAYAAN KADER REMAJA DALAM UPAYA PENINGKATAN PERILAKU GIZI SEIMBANG BAGI REMAJA: Pemberdayaan Kader Remaja di SMAN 01 Motui Kab. Konawe Utara - Rasmaniar, Rasmaniar; Fathurrahman, Teguh; Ahmad; Nurlaela, Euis; I Made Rai , Sudarsono (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2025)
Nutritional problems in adolescents include stunting, wasting, chronic energy deficiency, micronutrient deficiencies, anaemia and eating disorders. These problems can have an impact on reducing adolescent productivity and the risk of non-communicable diseases. This community service activity aims to empower adolescent posyandu cadres in improving balanced nutrition behaviour for adolescents with nutrition counselling methods for adolescent posyandu cadres. The results showed that the knowledge of adolescents before counselling was mostly in the poor category, namely 72.4% (n = 21), after counselling knowledge increased, more adolescents had knowledge in the good category, namely 48.3% (n = 14). There is an effect of empowering adolescent cadres with counselling methods to increase the knowledge of adolescent cadres about balanced nutrition.